(untitled) (Revista História & Perspectivas, 2011)
Em 1867 Karl Marx publicou o Livro I do Das Kapital (O Capital). Em 2005, José Saramago publicou As intermitências da morte. Um século e meio e dois pensadores que escolhem diferentes objetos como centro de sua reflexão: em Marx, o capital; em Saramago, a morte. A despeito das diferenças formais e substantivas entre uma teoria social e um romance, a construção de cada uma dessas estruturas, o capital e a morte, ilumina, pela sua semelhança, a compreensão da outra. Isso revela-se ainda ao atentar para a maneira como se processa socialmente a autonomização e crise dessas estruturas. É extremamente instigante trazer para a imaginação teórica, no atual momento de crise estrutural do capital, a imaginação romanesca de Saramago que começa assim: "No dia seguinte ninguém morreu". PALAVRAS-CHAVE: Saramago. Morte. Capital. ABSTRACT: In 1867 Karl Marx published volume I of Das Kapital (Capital). In 2005 José Saramago published As intermitências da morte (translated in English as "Death with interruptions"). One century and a half and two thinkers who choose different objects as the center of their reflections: in Marx, capital; in Saramago, death. Despite the formal and substantive differences between a social theory and a novel, the construction of each of these structures, capital and death, illuminates the understanding of the other one. This is also clear while paying attention to theway the autonomization and crisis of these structures is socially processed. It is extremely stimulating to bring to the theoretical imagination the novelistic imagination of Saramago, that begins: "The next day, no one died".This article has as objective the reflection on the long course covered by History until the historians incorporated to their investigation, not only what happened, but also the not carried though possibilities, and the utopia desire. This implied rethinking the ways of the historical narrative and its relations with literature, searching the overcoming of the Aristotelians opposition between truth and lie. That does not mean equate the fields of History and literature, but to consider them different forms of apprehension of equally different dimensions of the reality. It is not, therefore, to separate in literature its aspects of true and lie or in it searching given for objectives. More to look for answers, is to find in it the questions of a time. KEYWORDS: Saramago. Death. Capital.